Mitigating the Social Costs of the Economic Crisis and the Reform Programs in Asia - Verhoeven, Marijn (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1998)
This paper presents a preliminary analysis of the likely social impact of the economic crisis and the reform programs in three Asian countries-Indonesia, Korea, and Thailand. The focus is on likely changes in real consumption expenditures arising from higher inflation and increases in unemployment. The current social policy measures adopted in the reform programs should provide significant social safety nets for the poor. However, if the social impact turns out to be larger than projected, it would be worthwhile to assess cost-effective and efficient alternatives for expanding social safety nets. The paper presents some options that could be considered.